Improvement in Paretic Arm Reach-to-Grasp following Low Frequency Repetitive Transcranial Magnetic Stimulation Depends on Object Size: A Pilot Study - Jarugool Tretriluxana; Shailesh Kantak; Suradej Tretriluxana; Allan D. Wu; Beth E. Fisher (Stroke Research and Treatment)
Introduction. Low frequency repetitive transcranial magnetic stimulation (LF-rTMS) delivered to the nonlesioned hemisphere has been shown to improve limited function of the paretic upper extremity (UE) following stroke. The outcome measures have largely included clinical assessments with little investigation on changes in kinematics and coordination. To date, there is no study investigating how the effects of LF-rTMS are modulated by the sizes of an object to be grasped. Objective. To investigate the effect of LF-rTMS on kinematics and coordination of the paretic hand reach-to-grasp (RTG) for two object sizes in chronic stroke. Methods. Nine participants received two TMS conditions: real rTMS and sham rTMS conditions. Before and after the rTMS conditions, cortico-motor excitability (CE) of the nonlesioned hemisphere, RTG kinematics, and coordination was evaluated. Object sizes were 1.2 and 7.2 cm in diameter. Results. Compared to sham rTMS, real rTMS significantly reduced CE of the non-lesioned M1. While rTMS had no effect on RTG action for the larger object, real rTMS significantly improved movement time, aperture opening, and RTG coordination for the smaller object. Conclusions. LF-rTMS improves RTG action for only the smaller object in chronic stroke. The findings suggest a dissociation between effects of rTMS on M1 and task difficulty for this complex skill.